MENINGKATKAN KETERAMPILAN MENULIS PUISI DENGAN MENGGUNAKAN MEDIA GAMBAR DI KELAS V SDN KARANG PENANG OLOH 1 KARANG PENANG SAMPANG - Zeyniyah Zeyniyah (KOLONI, 2023)
This research is aimed to overcome the lack of the studying results of the writing poem subject in the class V SDN Karang Penang Oloh 1 Karang Penang Sampang ,by using picture and picture method it can make them easier in writing poems. The method that was used in this research was Descriptive method in form Classroom Action Research and collaborative by referred to the Classroom Action Research as, planning, observation, and reflection. The subject of this research was students of class V SDN Karang Penang Oloh 1 Karang Penang Sampang in this research were 25 students of class V semester 2 academic year 2017/2018. Data collecting techniques in this research were observation,data analysis, and average. This research result found there was improvement, (a ) teacher ability in making a planning to writing poem by using pictures and pictures model on cycle 1 is 2,28(good enough). In cycle 2 is 3,28 ( good ), then in cycle 3 is 3,55 ( very good ). (b) the teacher ability in implementing write poem by using picture and picture poem in cycle 1 is 3,15 (good enough), cycle 2 is 3,28 (good ), cycle 3 is 3,70 ( very good ). ( c ) increasing students' ability in write poem by using picture and picture model we can see in cycle 1 average = 67 (good enough), cycle 2 average = 71(good ),cycle 3 average = 80 ( very good ). In the other words, picture and picture model in this research in Bahasa indonesia in class V of SDN Karang Penang Oloh 1 Karang Penang Sampang is success. Keywords: Writing Skills, Drawing Models, Students